Complement Anaphylatoxins and Inflammatory Cytokines as Prognostic Markers for COVID-19 Severity and In-Hospital Mortality - Alosaimi, Bandar; Mubarak, Ayman; Hamed, Maaweya E.; Almutairi, Abdullah Z.; Alrashed, Ahmed A.; AlJuryyan, Abdullah; Enani, Mushira; Alenzi, Faris Q.; Alturaiki, Wael (Frontiers in Immunology, 2021)
COVID-19 severity due to innate immunity dysregulation accounts for prolonged hospitalization, critical complications, and mortality. Severe SARS-CoV-2 infections involve the complement pathway activation for cytokine storm development. Nevertheless, the role of complement in COVID-19 immunopathology, complement‐modulating treatment strategies against COVID-19, and the complement and SARS‐CoV‐2 interaction with clinical disease outcomes remain elusive. This study investigated the potential changes in the complement signaling and its associated inflammatory mediators in mild-to-critical COVID-19 patients and their clinical outcomes. The C3a, C5a, and factor P (properdin), as well as IL1-β, IL-6, IL-8, TNF-α, and IgM antibody levels, were higher in the critical COVID-19 patients than in the mild COVID-19 patients. Compared to the mild COVID-19 patients, factor I and C4-BP levels were significantly decreased in the critical COVID-19 patients. RANTES levels were significantly higher in the mild COVID-19 patients compared to critical COVID-19 patients. Furthermore, the critical COVID-19 intra-group analysis showed significantly higher C5a, C3a, and factor P levels in the critical COVID-19 non-survival group than in the survival group. Furthermore, the IL1-β, IL-6, and IL-8 levels were significantly upregulated in the critical COVID-19 non-survival group than in the survival group. The C5a, C3a, factor P, and the serum IL1-β, IL-6, and IL-8 levels correlated with those in the critical COVID-19 in-hospital death. These findings highlight the potential prognostic utility of the complement system for predicting COVID-19 severity and mortality and suggest that the complement anaphylatoxins and inflammatory cytokines are potential treatment targets against COVID-19 infections.